Tinjauan Hukum Islam Tentang Praktik Himpun Bah Pemekonan Sebelum Pelaksanaan Perkawinan dalam Adat Lampung Saibatin di Kabupaten Pesisir Barat - Indah Widiyansari; Zuhraini Zahda; Liky Faizal (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This collection of pemekonan is done 1 week before the wedding day. This research aims to analyze the practice of gathering bah pemekonan before marriage in the Lampung Saibatin tradition in Pesisir Barat Regency and to analyze the Islamic law review of gathering bah pemekonan before carrying out marriage in the Lampung Saibatin tradition in Pesisir Barat Regency. The results of the research show that the practice of gathering bah pemekonan before the implementation of the first marriage in Pesisir Barat Regency, there was an agreement/consensus after the gathering of muaghi was carried out. Second, notification to the entire community, traditional leaders, religious and government leaders door to door. Kegita, the implementation of the himpun bah pemekonan is carried out in the evening, before starting, a prayer is first made for the smooth running of the wedding event. Fourth, ask the King for permission to carry out the collection of bah pemekonan. Fifth, notification of the hajat to all people that the host will have a hajat. Sixth, consensus by traditional leaders. Seventh, bookkeeping regarding the contents of the Pemekonan bah collection. If it has been agreed by traditional leaders, then all the results of the Pemekonan bah collection are recorded in the book. Eighth, report to the King. Ninth, closing, then the collection of the pemekonan is closed by the host. Review of Islamic law, the practice of gathering bah pemekonan before marriage in the Lampung Saibatin custom in Pesisir Barat Regency is in accordance with Islamic law and is regulated in the Al-Qur'an and Hadith. In Islamic law, this is known as Sahih Urf because it fulfills the applicable rules. Himpun bah pemekonan is included in the category of maslahah al-Ammah, because it concerns the public interest/many people.